Efficacy of Bremelanotide for HSDD in Women: RECONNECT Open-Label Extension Phase Results [8Q]. (May 2018) - Clayton, Anita H.; Kingsberg, Sheryl A.; Simon, James A.; Jordan, Robert; Lucas, Johna
Abstract : INTRODUCTION: Bremelanotide, an investigational new drug, is a melanocortin 4 receptor agonist that has demonstrated efficacy in treatment of hypoactive sexual desire disorder (HSDD) in premenopausal women. The objective of this analysis was to evaluate sustained maintenance of bremelanotide effect on HSDD during the open-label extension (OLE) phase of the RECONNECT Study. METHODS: After completion of the double-blinded, placebo-controlled, core phase of RECONNECT (301 and 302 studies), premenopausal women with HSDD were eligible to enroll in the 52-week OLE. Bremelanotide 1.75 mg was self-administered as desired via auto-injector pen. Efficacy was assessed via FSFI and FSDS-DAO questionnaires. FSFI desire domain (FSFI-D) and FSDS-DAO distress resulting from low desire (Item 13) were co-primary endpoints. Data were collected during clinic visits occurring at 4- to 8-week intervals. OLE baselines for the bremelanotide and placebo groups were core study baseline and end of core study, respectively. RESULTS: For the 301 study OLE, 124 subjects from the bremelanotide arm and 239 subjects from the placebo arm were enrolled. At week 4, subjects who received bremelanotide or placebo in the core phase demonstrated respective mean changes from group baseline of 1.11 and 0.80 in FSFI-D, and -1.20 and -0.60 in FSDS-DAO Item 13. The 302 study had similar OLE results. For all subjects, improvements were consistently maintained until week 52. Similar trends were also observed for multiple secondary endpoints. CONCLUSION: Regardless of core phase treatment, bremelanotide provided treatment benefits in women with HSDD for the duration of the year-long RECONNECT OLE.